2020
DOI: 10.1136/bmjdrc-2019-000741
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of obesity to adipose tissue insulin resistance

Abstract: AimsThis study aimed to examine the association of different anatomical forms of obesity with adipose tissue insulin resistance and to assess the diagnostic value and contribution of obesity to adipose tissue insulin resistance.MethodsThis cross-sectional study included a total of 499 subjects aged 50 years or over. Multivariate regression analysis was conducted to clarify the association of different forms of obesity with adipose tissue insulin resistance (calculated as fasting insulin level×fasting free fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…To assess the contribution of each risk factor to the residual risk of new stroke, attributable risk percent (ARP) (1) and population attributable risk percent (PARP) (2) were calculated as follows [ 21 ]:…”
Section: Methodsmentioning
confidence: 99%
“…To assess the contribution of each risk factor to the residual risk of new stroke, attributable risk percent (ARP) (1) and population attributable risk percent (PARP) (2) were calculated as follows [ 21 ]:…”
Section: Methodsmentioning
confidence: 99%
“…Adiposity, particularly abnormal fat accumulation, is a key MetS-causing factor since it has a strong influence on insulin sensitivity and β-cell function and thereby increases the risks of CVD and T2D [ 7 , 8 ]. It was found that abdominal obesity accounted for approximately two-thirds of the strongest factors contributing to adipose tissue-derived insulin resistance (IR) in both men and women [ 9 ]. Since IR will lead to a gradual progression from hyperinsulinemia to glucose intolerance and eventually, T2D [ 10 ], the early detection of MetS risks (including IR) is important for the prevention of chronic metabolic diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that abdominal obesity accounted for approximately two-thirds of the strongest factors contributing to adipose tissue-derived insulin resistance (IR) in both men and women [ 9 ]. Since IR will lead to a gradual progression from hyperinsulinemia to glucose intolerance and eventually, T2D [ 10 ], the early detection of MetS risks (including IR) is important for the prevention of chronic metabolic diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact etiology of the MetS is not clearly understood, insulin resistance (IR) is considered as the principal factor for the pathogenesis of this syndrome [ 6 , 11 , 18 , 45 ]. As found by the insulin-modified, frequently sampled intravenous glucose tolerance assay, insulin sensitivity is significantly lower in patients with two or more components of the MetS compared to those with none of these components [ 2 ].…”
Section: Metabolic Syndrome: Definitions and Criteriamentioning
confidence: 99%